Book review: Aneela Zeb Babar, We Are All Revolutionaries Here: Militarism, Political Islam and Gender in Pakistan. Issue 2 (December 2017) - Sengupta, Sucharita
Aneela Zeb Babar, We Are All Revolutionaries Here: Militarism, Political Islam and Gender in Pakistan . New Delhi: SAGE Publications and Yoda Press, 2017, xii + 180 pp., ₹695.